Advances in child development and behavior. Volume 8 - Reese, Hayne W. (Academic Press, 1973)
Presents 6 documented, critical reviews of recent findings in child learning and behavior. Topics include elaboration and learning in childhood and adolescence, exploratory behavior and human development, operant conditioning of infant behavior, birth order and parental experience in monkeys and man, fear of strangers in children, and the application of the Hull-Spence theory to discrimination learning in children.